Roman epic: an interpretative introduction - Albrecht, Michael von (Mnemosyne, bibliotheca classica Batava. Supplementum, 1999)
Preliminary Material /Michael von Albrecht -- Introduction /Michael von Albrecht -- Livius Andronicus /Michael von Albrecht -- Naevius /Michael von Albrecht -- Ennius /Michael von Albrecht -- Virgil /Michael von Albrecht -- Ovid /Michael von Albrecht -- Albinovanus Pedo /Michael von Albrecht -- Cornelius Severus /Michael von Albrecht -- Lucan /Michael von Albrecht -- Valerius Flaccus /Michael von Albrecht -- Statius /Michael von Albrecht -- Silius Italicus /Michael von Albrecht -- Claudian /Michael von Albrecht -- Corippus /Michael von Albrecht -- Bibliography /Michael von Albrecht -- List of Abbreviations: Periodicals and Standard Works /Michael von Albrecht -- Index /Gregor Damschen -- Supplements to Mnemosyne /J. M. Bremer , L. F. Janssen , H. Pinkster , H. W. Pleket , C. J. Ruijgh and P. H. Schrijvers.